Impedance control approach in robot’s leg dragging velocity variations - Lezaini, -; W. M., N. W.; Addie Irawan, Hashim (2018)
One of the challenging areas in developing bio-inspired legged robot is dynamic control, especially in environment interaction. Impedance control are widely used by researchers for dynamic interaction, but majority only focus on adapting uneven terrain structure. This idea may not be suitable for pick-and-place task robot that have varied weight due to its body weight and payload as well as locomotion on flat terrain. Thus, this paper presents leg motion speed control through impedance control approach with aim to increase energy of the legged robot especially during leg dragging based on force on contact. The results show that proposed controller is applicable since it increase the energy and velocity of leg motion due to increase in force on contact while maintaining shape of the leg motion.